Radiocarbon Pretreatment Comparisons of Bald Cypress (Taxodium Distichum) wood samples from a massive buried deposit on the Georgia Coast, USA. Issue 6 (11th October 2019) - Napora, Katharine G; Cherkinsky, Alexander; Speakman, Robert J; Thompson, Victor D; Horan, Robert; Jacobs, Craig
ABSTRACT: We sampled individual growth rings from three ancient remnant bald cypress ( Taxodium distichum ) trees from a massive buried deposit at the mouth of the Altamaha River on the Georgia Coast to determine the best technique for radiocarbon ( 14 C) dating pretreatment. The results of our comparison of traditional ABA pretreatment and holocellulose and α-cellulose fractions show no significant differences among the pretreatments (<1 sigma) thereby suggesting that ABA pretreatment will prove sufficient for the development of a high-resolution 14 C tree-ring chronology based on these ancient bald cypresses which will indicate whether the U.S. Southeast is subject to a regional radiocarbon offset.